What Role Can Open Science Play In Enabling Global Knowledge Exchange? - Havemann, Johanna; Ahinon, Justin Sègbédji (My University, 2019)
Global threats and challenges resulting from climate change and political crises call for a new agenda to find solutions that work for not just a few but the global community. To provide more visibility and more opportunities to world-wide scientific discussions to African scientists the region-specific preprint repository AfricArXiv.org is meant to trigger interdisciplinary research within the continent as well as globally with research institutions overseas. The repository is a platform for African scientists to publish their research output immediately and free of cost. This makes it possible for them to receive feedback on their work, improve the manuscript for submission to a peer-reviewed journal and identify potential collaboration partners for future projects. Researchers in Africa, Latin America and Southeast Asia now have the opportunity to find up to date research results through online publishing systems, databases and scientific service providers, make their own research output more visible and build transcontinental collaborations more effectively. We propose that practiced Open Science allows for more diversity in research output and the convergence of the global scientific community. In this discussion, we will address, based on the different experiences with the initiatives mentioned above, how open science can help to facilitate collaboration and the dissemination of knowledge between North and South.
Keywords: Research in Africa; Open Science; Africa